Pre-harvest desiccation in biomass sorghum with herbicides - de Barros, Angélica Fátima; Duarte Pimentel, Leonardo; Lopes de Freitas, Francisco Cláudio; Cecon, Paulo Roberto; Cirino Tomaz, Adriano; Biesdorf, Evandro Marcos (Revista Ceres, 2025)
The purpose of this study was to assess the effect of different herbicide treatments on moisture removal and calorific power of biomass sorghum for co-generation of electric energy through burning. The experiment was conducted in randomized complete block design with four replicates per treatment and a 6x4 factorial scheme (six herbicide treatments x four intervals between spraying and harvesting). The herbicide treatments were: two different doses of glyphosate (1.92 kg a.i. ha-1 and 3.84 Kg a.i. ha-1), paraquat (0.4 Kg a.i. ha-1), a commercial mixture of paraquat + diuron (0.6 + 0.3 Kg a.i. ha-1), glufosinate-ammonium (0.8 Kg a.i. ha-1) and control (unsprayed). The intervals between spraying and harvesting assessed were 7, 14, 21 and 28 days after desiccation (DAD). It was assessed: the number of leaves per plant, moisture content of leaves, panicles, culm and whole ground plants and Superior Calorific Power (SCP). The herbicides paraquat and paraquat + diuron promotes defoliation, after 14 DAD. Glyphosate, paraquat, paraquat + diuron and glufosinateammonium reduce leaf and panicle moisture, despite only glyphosate reduces moisture in the culm. The herbicides do not affect the SCP of biomass sorghum. Therefore, the herbicides, especially glyphosate, have high potential for preharvest desiccation in biomass sorghum.